(3ejKGb GdfSGAs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s ((3MeRg Hf Ydj Hf CMeO s)
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdMGce SHMGfg s
(3BNQgG (B:s
(3hGdMeO dehdGfG MeO GdTGcQjf hgh MSHj hfYe GdfUjQ GdoeYjf JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B8s
(3GdfSNI HgG MhGTs
(3QSGdI ef QSGFd GdOQhRs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI aj HjQhJ s
Keywords: (3GdJhMjO hGdedd hGdfMds